Management Strategy for Anchovies (Stelephorus Sp) at Batu Belubang Fishing Port, Central Bangka Regency - Wiseli, Retfi; Ferizal, Jemi (Akuatik: Jurnal Sumberdaya Perairan, 2024)
The marine and fisheries sector plays a vital role in national development, particularly as a major source of employment across various stages, from fishing and aquaculture to processing, distribution, and marketing of fishery products. As such, this sector requires focused governmental attention across the entire value chain, from upstream to downstream. In Batu Belubang Village, Bangka Regency, the local fishing catch is dominated by anchovies (Stolephorus sp.). According to a report from Babel Today (September 28, 2024), this abundance raises a critical question: is it a blessing or a burden for local fishermen? To support the sustainable development of the anchovy value chain and align production with consumer demand, this study seeks to formulate a strategic management approach for anchovy resources at the Batu Belubang Fishing Port. Fieldwork was conducted in October 2024. The study employed qualitative methods, gathering primary data through interviews with fishing vessel owners, small-scale fish processors, and the head of the Batu Belubang Fishing Port. Secondary data were obtained through literature reviews, including scholarly journals, books, online resources, and mass media coverage. A SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis was applied to assess resource potential and identify development constraints. The study concludes that enhancing the anchovy-based fisheries sector requires an integrated approach that includes: promoting the national “Love Eating Fish” campaign (GEMARIKAN) with a specific focus on anchovy products; providing technical training and support for local fish processing with appropriate technological innovation; extending the Batu Belubang port pier to improve infrastructure; and revising fishing quota policies to support sustainability and market efficiency.